Analyzing Trends and Profitability Vis-Ã€-Vis Working Capital Management (WCM): A Study of Select Information Technology (IT) Organizations in India - Chandra, Bibhas; Chouhan, Vineet; Goswami, Shubham (Indian Journal of Finance, 2012)
In the prevalent business milieu, where the companies are fighting tooth and nail to gain market pie, managing financial resources is the Hobson's choice for continued existence. Working capital management is an integral component of corporate strategy for managing overall financial resources. However, the appropriateness of working capital management is rooted to its potency to Institute trade-off between liquidity and profitability. The IT industry in India has ousted the growth pattern of other sectors and is witnessing a relatively steep growth rate. Moreover, the industry is equally growing in size with the incorporation of new companies day after day. Consequently, the companies are caught in pincers due to the burgeoning competition outwardly, and financial resources restrain within. A plethora of research works in the related area has been so far undertaken in the manufacturing sector; however, the service industry is largely ignored. Thus, this study makes an attempt to analyze the size, composition and trends in working capital employed by select Indian IT companies. The study employs correlogram analysis of time series data for ten years corresponding to WC of each select IT company. The analysis estimates an increased requirement of WC in the future for IT companies in India. In addition, the study investigates the significance of relationship between profitability and working capital employed by the select IT companies. The value of Pearson Correlation coefficient corresponding to each company signifies a positive relationship between WC and Profitability largely.